Are youth sport talent identification and development systems necessary and healthy? - Fieke Rongen; Jim McKenna; Stephen Cobley; Kevin Till (SpringerOpen, 2018)
Abstract Talent identification and development systems (TIDS) are commonly used in professional sport to convert youth athletes into sporting stars of the future. Acknowledging that only a few athletes can "make it," the necessity and healthiness of TIDS have recently been questioned based on their increased professionalism, high training, and competition volumes, but limited effectiveness. In this short communication, we suggest that the key issues associated with TIDS are not due to their overall concept, but with how they are designed and implemented. It is recommended that researchers and practitioners determine the worth and value of TIDS by also evaluating the positive health of the athlete rather than solely focusing on performance outcomes. To achieve this, TIDS staff should shape and develop their values, expectations, and day-to-day routines to achieve positive health outcomes focusing on personal development and an athlete-centered culture. In business, this has been termed the concept of "Deliberately Developmental Organisation." TIDS can deploy the factors (e.g., high-quality staff, expert support services, quality facilities, and learning routines) characteristic of such organizations, to concurrently ensure positive impacts and minimize predictable negative outcomes without losing focus on a drive for sporting performance.